Exploring undergraduates' experiences of teaching and learning in a Chinese-Australian programme: An intercultural dialogue perspective - Zhao, Xiantong; Liu, Xu (Technium Social Sciences Journal, 2022)
This study aims to explore and understand undergraduates’ experiences of teaching and learning in a Chinese-Australian collaborative programme. Data are collected mainly through in-depth interviews with 23 Chinese students and supplemented by classroom observation and document analysis. The findings reveal that although teaching and assessment differs between the Chinese and Western lecturers, the Chinese lecturers are Westernising their teaching and assessment methods. While many students preferred the Australian system of teaching and assessment, a few still favoured the Chinese methods of instruction and evaluation. Furthermore, the design of the curriculum proved problematic due to parts of it being irrelevant and failing to meet the students’ needs and expectations; some students also found fault with the intensity of the course schedule. The findings are further explored in the light of the intercultural dialogue (ICD) framework.